Shades of grey—tire characteristics and road surface influence tire and road wear particle (TRWP) abundance and physicochemical properties - Wilkinson, Tim; Järlskog, Ida; de Lima, Juliana Aristéia; Gustafsson, Mats; Mattsson, Karin; Andersson Sköld, Yvonne; Hassellöv, Martin (Frontiers in Environmental Science, 2023)
There is mounting evidence that tire wear particles can harm natural systems, but worldwide trends in car weight and car usage, mean emissions are set to increase. To control tire wear emissions and help understand fate and transport, detailed characterisation of the particles, and the relationship between road surface properties and emission profiles is needed. This study deployed a suite of experiments utilising the advanced road simulator of the Swedish National Road and Transport Research Institute to compare seasonal tire types from three brands. An extraction method was developed for a coarse (>30 µm) fraction of tire and road wear particles (TRWP), and a comprehensive physicochemical characterisation scheme applied to both TRWP and tire-tread, including microscopy, energy-dispersive X-ray spectroscopy and pyrolysis-GC/MS. Road simulator dusts and hand-picked TRWP showed differences in shape, numbers, and mass between tire types and brands, and between asphalt and cement concrete road surfaces. Contrary to accepted perceptions, tactile analyses revealed that firmelastic TRWP comprised only a minor proportion of TRWP. Fragile and chemically distinct tire-roadderived particles, termed here sub-elastic TRWP, comprised 39-100 % of TRWP. This finding raises urgent questions about overall TRWP classification and identification features, resistance to This is a provisional file, not the final typeset article weathering, and environmental fate. At the same time, differences in TRWP generation between tire formulations, and road surfaces, show potential for controlling emissions to reduce global impacts.